Substrate-induced closure of the flap domain in the ternary complex structures provides insights into the mechanism of catalysis by 3-hydroxy-3-methylglutaryl–CoA reductase - Tabernero, Lydia (The National Academy of Sciences, 1999)
3-hydroxy-3-methylglutaryl–CoA (HMG-CoA) reductase is the rate-limiting enzyme and the first committed step in the biosynthesis of cholesterol in mammals. We have determined the crystal structures of two nonproductive ternary complexes of HMG-CoA reductase, HMG-CoA/NAD(+) and mevalonate/NADH, at 2.8 Å resolution. In the structure of the Pseudomonas mevalonii apoenzyme, the last 50 residues of the C terminus (the flap domain), including the catalytic residue His381, were not visible. The structures of the ternary complexes reported here reveal a substrate-induced closing of the flap domain that completes the active site and aligns the catalytic histidine proximal to the thioester of HMG-CoA. The structures also present evidence that Lys267 is critically involved in catalysis and provide insights into the catalytic mechanism.